Diversity and antibiotic resistance patterns of sphingomonadaceae isolates from drinking water - Vaz-Moreira, Ivone (2012)
Sphingomonadaceae (n = 86) were isolated from a drinking water treatment plant (n = 6), tap water (n = 55), cup fillers for dental chairs (n = 21), and a water demineralization filter (n = 4). The bacterial isolates were identified based on analysis of the 16S rRNA gene sequence, and intraspecies variation was assessed on the basis of atpD gene sequence analysis. The isolates were identified as members of the genera Sphingomonas (n = 27), Sphingobium (n = 28), Novosphingobium (n = 12), Sphingopyxis (n = 7), and Blastomonas (n = 12). The patterns of susceptibility to five classes of antibiotics were analyzed and compared for the different sites of isolation and taxonomic groups. Colistin resistance was observed to be intrinsic (92%). The highest antibiotic resistance prevalence values were observed in members of the genera Sphingomonas and Sphingobium and for beta-lactams, ciprofloxacin, and cotrimoxazole. In tap water and in water from dental chairs, antibiotic resistance was more prevalent than in the other samples, mainly due to the predominance of isolates of the genera Sphingomonas and Sphingobium. These two genera presented distinct patterns of association with antibiotic resistance, suggesting different paths of resistance development. Antibiotic resistance patterns were often related to the species rather than to the site or strain, suggesting the importance of vertical resistance transmission in these bacteria. This is the first study demonstrating that members of the family Sphingomonadaceae are potential reservoirs of antibiotic resistance in drinking water.